Application of stem-based on flipped learning in natural sensitivity courses - Misbach, M. Misbachul Huda; Putri Rilianti, Adhy (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The research aims to describe the application of flipped learning-based STEM in Sensitivity to Nature courses for PGSD students. The method used in this research is descriptive qualitative. The research data is described in the form of a description that describes the application of STEM-based on Flipped Learning in Sensitivity of Nature course. The application of STEM-based flipped learning in Sensitivity of Nature courses is carried out in 4 phases, the independent learning phase through LMS, the phase of completing assignments in the online class, the discussion phase in the online class, and the understanding test phase in the class through the LMS. STEM components are mapped based on the constituent subjects of STEM, science, technology, engineering, and mathematics. The results of mapping become a reference in the preparation of lecture materials and activities. The results of this study imply that the application of STEM-based flipped learning can be applied to courses that have a relationship with STEM subjects.